Effects of different cooking methods on some chemical and sensory properties of Galega kale. (14th July 2016) - Armesto, Jorge; Gómez‐Limia, Lucía; Carballo, Javier; Martínez, Sidonia
Summary: Kale ( Brassica oleracea L. var. acephala ) is rich in bioactive phytochemicals such as phenolic compounds and vitamins. However, cooking the plants can cause important changes in composition. The objective of this study was to investigate the effect of some domestic cooking processes (boiling, steaming, microwaving and pressure cooking) on several quality parameters of Galega kale. Boiling had the strongest effect on the antioxidant capacity (the IC50 was four times higher than in the fresh sample), total phenolics (losses of 76.4–77.9%) and colour (Δ E = 17.79–19.12). Microwaving caused the greatest loss of soluble solids (80.8–82.2%). Steaming seems to be the best method for retaining the nutrient and antioxidant capacity of kale (100% ash, 71–77.5% soluble solids, 100% antioxidant capacity, 67–71% total phenolics, 62–71% chlorophyll). However, steamed kale was awarded the lowest sensory scores, indicating the difficulty in reconciling nutritional value and sensorial quality. Use of discriminant statistical techniques enabled the classification of 100% of samples. Abstract : Effects of different cooking on Galega kale